PREFERENSI GENERASI MILENIAL DALAM BERINVESTASI DI PASAR MODAL SYARIAH - Nurizka, Rifda; Noor, Iswan (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
Investors in the Islamic capital market record growth every year. However, the total sharia investors compared to the total investors as a whole in 2021 is still at 5.5%. Whereas Indonesia has great potential in the Islamic capital market with 86.88% of Indonesian Muslims in 2021. So, this study aims to determine the effect of Islamic financial literacy, income, technology advance and risk perception on investment preferences in the Islamic capital market in millennial generation at Malang. The method to collected the data in this study is through questionnaire distributed by google form. The technique to collected data used in this study is purposive sampling with total of 107 respondents who were born in 1981 – 1996, domiciled in Malang and had invested in the Islamic capital market after March 2020. The data analysis method used was logistic regression analysis using a logistic regression analysis tool with SPSS. The results of this study indicate that Islamic financial literacy, technology advance and risk perception do not have a significant influence on investment preferences in the Islamic capital market, while income has a significant influence on investment preferences in the Islamic capital market.